Pengaruh Nilai Impor Dan Realisasi Penerimaan Bea Masuk Terhadap Target Penerimaan Bea Masuk Pada Kantor Pengawasan Dan Pelayanan Bea Dan Cukai Tipe Madya Pabean A Kota Tangerang Selatan - Chaerina Chaerina; Irwin Ananta Vidada; Seno Sudarmono Hadi (Sekolah Tinggi Ilmu Ekonomi Trianandra, 2023)
In the current era of economic development, Indonesia is focused on how the government maximizes state revenues, government agencies or the Directorate General of Customs and Excise need to expand performance or targets in order to face economic competition, that import duty receipts at KPPBC A South Tangerang City in 2020-2022 did not reach the target set by the State Budget which is still increasing and decreasing. This study aims to see how much influence the value of imports and the realization of import duty receipts on the target of partial and simultaneous import duty receipts. The study used a quantitative approach, information in the form of secondary data, namely time series data totaling 36 samples, data collection techniques using obseration and documentation. This study used the classical assumption test analysis method of multiple linear regression with SPSS. The acquisition of research shows that the value of imports has a positive and significant effect on the target of import duty receipts, while the realization of import duty receipts has a positive and insignificant effect on the target of import duty receipts. Simultaneously, the value of imports and the realization of import duty receipts have a significant effect on the target of import duty receipts at KPPBC A South Tangerang City. For future researchers, it is better to conduct studies in more than one region or port so that the results of the study can represent the overall condition in Indonesia in order to obtain accurate, representative and complete data so that the analysis and findings in the study become more valid.